Child Risk Determinants to Predict Stunting: A Case-Control Study in Sorawolio, Bau-Bau City - Fitri Rachmillah Fadmi; Sri Mulyani; Asfani Yuhadi; Wa Ode Justin (YCAB Publisher, 2026)
Background: Stunting remains a major public health concern with serious consequences for human development and long-term productivity. Objective: This study analyzed child-related factors linked to stunting among children under five in the Sorawolio Health Center area, Baubau City, and developed a logistic regression prediction model. Methods: Using a case-control design, the researchers included 302 participants 151 stunted and 151 non-stunted children selected through proportional random sampling. Health center records provided the child's nutritional status, while structured interviews with a validated questionnaire collected data on birth order, low birth weight (LBW), birth length, immunization history, exclusive breastfeeding, and household exposure to cigarette smoke. Results: Multivariate logistic regression showed strong associations between stunting and being the firstborn (AOR=7.45; 95% CI: 3.64–15.26), LBW (AOR=7.16; 95% CI: 1.60–32.13), short birth length <48 cm (AOR=25.29; 95% CI: 11.51–55.55), absence of exclusive breastfeeding (AOR=9.10; 95% CI: 3.17–26.15), and cigarette smoke exposure (AOR=2.40; 95% CI: 1.21–4.79). Immunization status showed only a borderline effect (p=0.059). The final model (constant –16.712) indicated that stunting risk rises sharply when multiple risk factors occur together, supporting its use as an early screening tool in primary care. Conclussion: These findings highlight how biological, nutritional, and environmental factors interact to drive stunting and emphasize the urgency of targeted interventions in coastal communities with limited health resources.